The effects of haloperidol on motor vigour and movement fusion during sequential reaching. - Sebastian Sporn; Joseph M Galea (PLoS ONE)
Reward is a powerful tool to enhance human motor behaviour with previous research showing that during a sequential reaching movement, a monetary incentive leads to increased speed of each movement (motor vigour effect), whilst reward-based performance feedback increases the speed of transition between movements (movement fusion effect). The neurotransmitter dopamine plays a central role in the processing of reward signals and has been implicated to modulate motor vigour and regulate movement fusion. However, in humans, it is unclear if the same dopaminergic mechanism underlies both processes. To address this, we used a complex sequential reaching task in which rewards were based on movement times (MT). Crucially, MTs could be reduced via: 1) enhanced speed of individual movements (motor vigour effect) and/or 2) enhanced speed of transition between movements (movement fusion effect). 95 participants were randomly assigned to a reward or no reward group and were given either 2.5mg of the dopamine antagonist haloperidol or a placebo (control group). An independent decision-making task performed prior to the main experiment suggested that haloperidol was active during the sequential reaching task (positive control). We did not find evidence that haloperidol affected the facilitatory effects of reward on movement fusion. However, we found that haloperidol negated the reward-based effects on motor vigour. Therefore, our results suggest that a D2-antagonist differentially influences reward-based effects on movement vigour and movement fusion, indicating that the dopaminergic mechanisms underlying these two processes may be distinct.